Enzymatic profiling in prostate and breast cancer cells: phosphate hydrolysis and alcohol oxidation. Issue 46 (17th November 2016) - Gonçalves, Caroline C.S.; da Costa, Bruna Z.; Lima, Maria L.S.O.; Fiorito, Giovanna F.; Ruiz, Ana Lúcia T.G.; de Oliveira, Silvia B.P.; Barbosa, Guilherme O.; de Carvalho, Hernandes F.; Marsaioli, Anita Jocelyne
Abstract: Enzyme activities in non-tumor and cancer cells, in different cell compartments, were visualized with two small fluorogenic probes: 7-(3-hydroxypropyl)-resorufin (7 ) and 7-(3-phosphatepropyl)-resorufin (9 ), with a primary alcohol and a phosphate group as enzymatic recognition sites. The designed probes were evaluated by in vitro assays, proving that both were biotransformed by their respective enzymes (probe7 by alcohol dehydrogenases, ADHs, and probe9 by a protein serine/threonine phosphatase, PSTP). Additionally, joint action of both enzymes (ADH and PSTP) revealed that probe9 underwent a multi-enzymatic cascade and that phosphate hydrolysis is the rate-limiting step. These probes were evaluated in four human cell lines: prostate cancer cells (PC-3), prostate cells (RWPE-1), breast cancer cells (MCF-7 BUS) and breast cells (MCF-10A). Flow cytometry experiments showed distinct profiles for prostate and breast cells and assays with phosphatase inhibitors confirmed the proposed multi-enzymatic cascade in living cells. Graphical abstract: